Targeted drug release from stable and safe ultrasound-sensitive nanocarriers - Wilson, Matthew G.; Parikh, Aarav; Dara, Audri; Beaver, Alexander S.; Kubanek, Jan (Frontiers in Molecular Biosciences, 2024)
Targeted delivery of medication has the promise of increasing the effectiveness and safety of current systemic drug treatments. Focused ultrasound is emerging as noninvasive and practical energy for targeted drug release.However, it has yet to be determined which nanocarriers and ultrasound parameters can provide both effective and safe release. Perfluorocarbon nanodroplets have the potential to achieve these goals, but current approaches have either been effective or safe, but not both. We found that nanocarriers with highly stable perfluorocarbon cores mediate effective drug release so long as they are activated by ultrasound of sufficiently low frequency. We demonstrate a favorable safety profile of this formulation in a non-human primate. To facilitate translation of this approach into humans, we provide an optimized method for manufacturing the nanocarriers. This study provides a recipe and release parameters for effective and safe drug release from nanoparticle carriers in the body part specified by focused ultrasonic waves.